Process simulation and economic analysis of biodiesel production from waste cooking oil with membrane bioreactor - Abdurakhman, Y.B. (American Institute of Physics Inc., 2017)
Pollution and shortage of clean energy supply are among major problems that are caused by rapid population growth. Due to this growth, waste cooking oil is one of the pollution sources. On the other hand, biodiesel appears to be one of the most promising and feasible energy sources as it emits less toxic pollutants and greenhouse gases than petroleum diesel. Thus, biodiesel production using waste cooking oil offers a two-in-one solution to cater pollution and energy issues. However, the conventional biodiesel production process using homogeneous base catalyst and stirred tank reactor is unable to produce high purity of biodiesel from waste cooking oil. It is due its sensitivity to free fatty acid (FFA) content in waste cooking oil and purification difficulties. Therefore, biodiesel production using heterogeneous acid catalyst in membrane reactor is suggested. The product of this process is fatty acid methyl esters (FAME) or biodiesel with glycerol as by-product. This project is aimed to study techno-economic feasibility of biodiesel production from waste cooking oil via heterogeneous acid catalyst in membrane reactor. Aspen HYSYS is used to accomplish this aim. Several cases, such as considering different residence times and the production of pharmaceutical (USP) grade glycerol, are evaluated and compared. Economic potential of these cases is calculated by considering capital expenditure, utilities cost, product and by-product sales, as well as raw material costs. Waste cooking oil, inorganic pressure-driven membrane and WAl is used as raw material, type of membrane and heterogeneous acid catalyst respectively. Based on literature data, FAME yield formulation is developed and used in the reactor simulation. Simulation results shows that economic potential increases by 30 if pharmaceutical (USP) grade glycerol is produced regardless the residence time of the reactor. In addition, there is no significant effect of residence time on the economic potential. © 2017 Author(s).